PENGARUH STATUS EKONOMI SOSIAL DENGAN PERKEMBANGAN KOGNITIF YANG DIUKUR DENGAN TES KEMAMPUAN BAHASA PADA ANAK USIA DINI - Neni Farida; Lina Marlina; Ida Nurhayati (Jurnal Anak Bangsa, 2023)
The purpose of this article is to document the relationship between socioeconomic status and cognitive development, as measured by tests of children's language skills at school. The language ability test consists of different listening abilities and speaking abilities of young children in two schools. The general objective of this study was to determine the relationship between socio-economic status and cognitive development as measured by language proficiency tests. The method in this research uses observation and questionnaire methods. The results of the data analysis show that in general a conclusion can be drawn: the relationship between socio-economic status and cognitive development as measured by tests of language skills which consist of listening and speaking abilities of different early childhood students in two schools both show that listening skills are higher compared to speaking ability. So if listening ability is given treatment, speaking ability will also be high